The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4025/actascianimsci.v41i1.44392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different sources of selenium supplementation on antioxidant indices, biochemical parameters, thyroid hormones and Se status in transition cows

Abstract: The aim of this study was to determine the effects of supplementing close-up and fresh dairy cows' diets with sodium selenite or organic sources of selenium (Se) on the serum biochemical parameters and antioxidant indicators and Se status. Twenty-four multiparous Holstein dairy cows were balanced by body condition score (BCS), previous lactation milk yield and expected calving date and randomly assigned to 1 of 4 experimental treatments. Treatments were: control (basal diet without Se supplementation), sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
2
7
0
1
Order By: Relevance
“…Similar results were detected previously in Jersey cows supplemented with Se-yeast during the last eight weeks of gestation [14] and in Holstein cows supplemented with selenomethionine from 21 days prepartum to 21 days post-partum [41] or inorganic Se + vitamin E [42].…”
Section: Selenium Bioforti Ed Hay Improves Albumin Production By the supporting
confidence: 89%
See 1 more Smart Citation
“…Similar results were detected previously in Jersey cows supplemented with Se-yeast during the last eight weeks of gestation [14] and in Holstein cows supplemented with selenomethionine from 21 days prepartum to 21 days post-partum [41] or inorganic Se + vitamin E [42].…”
Section: Selenium Bioforti Ed Hay Improves Albumin Production By the supporting
confidence: 89%
“…To further complicate the interpretation of the urea data, an increase in blood urea concentration in Se supplemented animals was also observed in rats supplemented with inorganic Se [48] and in one year old Angus steers fed organic Se [49] but not in multiparous dairy cows [41,50]. Thus, it is possible that the observed increased circulating urea by feeding Se-bioforti ed hay might only be associated with the young age of the cows used.…”
Section: Selenium Bioforti Ed Hay Improves Albumin Production By the mentioning
confidence: 99%
“…Next to this, several observational patient studies showed a positive correlation between Se and albumin levels [ 42 , 43 ], which was substantiated by in vivo evidence showing that Se supplementation increased albumin concentration [ 44 ]. However, residual confounding or a reverse association (i.e., low albumin leads to low Se levels) cannot be excluded, as approximately 10% of the total serum Se binds to albumin [ 42 ].…”
Section: Discussionmentioning
confidence: 88%
“…Another study showed that supplemental SM resulted in higher GPx1 and superoxide dismutase activities and increased plasma Se compared to SS (Sun et al 2019). However, in a more recent study, although Se plasma levels were increased more in cows fed Se-yeast and SM compared to those fed SS, no effects on biochemical antioxidant parameters were observed (Khalili 2019).…”
Section: Discussionmentioning
confidence: 90%